A compact light-sheet microscope for the study of the mammalian central nervous system - Yang, Z; Haslehurst, P; Scott, S; Emptage, N; Dholakia, K (Nature Publishing Group, 2016)
Investigation of the transient processes integral to neuronal function demands rapid and high-resolution imaging techniques over a large field of view, which cannot be achieved with conventional scanning microscopes. Here we describe a compact light sheet fluorescence microscope, featuring a 45° inverted geometry and an integrated photolysis laser, that is optimized for applications in neuroscience, in particular fast imaging of sub-neuronal structures in mammalian brain slices. We demonstrate the utility of this design for three-dimensional morphological reconstruction, activation of a single synapse with localized photolysis, and fast imaging of neuronal Ca2+ signalling across a large field of view. The developed system opens up a host of novel applications for the neuroscience community.